Gemella haemolysans as an emerging pathogen for bacteremia among the elderly. (5th October 2021) - Kodaka, Satoko; Uchida, Takuro; Gomi, Harumi
Abstract: We report a patient of an 82‐year‐old woman with occult Gemella haemolysans bacteremia without a clear entry site. Gemella haemolysans is part of the normal human flora but can cause severe systemic infections such as infective endocarditis on rare occasions. In this patient, physical examination showed no localized symptoms, and a transthoracic echocardiogram showed no vegetation on the heart valves. The entry site for this pathogen was unclear. As the number of the elderly with asymptomatic infections has been increasing, clinicians should be aware of that this microorganism can cause occult bacteremia and infective endocarditis.